Point-of-Care Early Infant Diagnosis Improves Adherence to the Testing Algorithm in Kenya. (12th February 2020) - Odhiambo, Collins Otieno; Githuka, George; Bowen, Nancy; Kingwara, Leonard; Onsase, Jared; Ochuka, Bernard; Waweru, Michael; Masaba, Rose; Matu, Lucy; Mwangi, Eliud; Cohn, Jennifer
Introduction: We determine the level of adherence to the revised Kenya early infant diagnosis (EID) algorithm during implementation of a point-of-care (POC) EID project. Methods: Data before (August 2016 to July 2017) and after (August 2017 to July 2018) introduction of POC EID were collected retrospectively from the national EID database and registers for 33 health facilities. We assessed the number of HIV-infected infants who underwent confirmatory testing and received baseline viral load test and proportion of infants with an initial negative result who had a subsequent test. Results and Discussion: Significantly higher number of infants accessed confirmatory testing (94.2% versus 38.6%; P < .0001) with POC EID. Baseline viral load test and follow-up testing at 6 months, although higher with POC EID, were not significantly different from the pre-POC EID intervention period. Conclusion: The POC EID implementation has the potential to increase proportion of infants who receive confirmatory testing, thus reducing the risk of false-positive results.